2021
DOI: 10.1155/2021/6696945
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of Textile‐Reinforced Concrete Beams versus Steel‐Reinforced Concrete Beams

Abstract: There has been a rising interest in utilising textile reinforcement such as carbon tows in constructing concrete components to enhance the performance of conventional reinforced concrete. Textile-reinforced concrete (TRC) has been used as a construction material mostly as primary reinforcement. However, the structural performance of TRC members has not been investigated in depth. Therefore, to better understand TRC beams’ behaviour under bending load, a widespread experimental investigation was conducted. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…TRC beams have 56% higher moment capacity and 7 times higher tension stiffening than SRC beams. Given these observations, TRC beams behave differently from SRC beams [11]. Due to its mechanical properties, light weight, energy absorption, and extremely high strength under impact loads, TRF concrete is being used in many sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…TRC beams have 56% higher moment capacity and 7 times higher tension stiffening than SRC beams. Given these observations, TRC beams behave differently from SRC beams [11]. Due to its mechanical properties, light weight, energy absorption, and extremely high strength under impact loads, TRF concrete is being used in many sectors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In recent studies, concrete beams made with textile reinforcement are compared with the conventional steel reinforced concrete beam. Alrshoudi (2021) observed that TRC beams with carbon textile reinforcement have a 56% higher moment capacity than steel reinforced concrete beams. In another study, You et al (2020) found that TRC showed improved flexural behavior and better-distributed crack patterns than conventional steel reinforced concrete specimens.…”
Section: Introductionmentioning
confidence: 98%
“…With the growing interest in cost-effective structural solutions, studies to find steel reinforcement’s alternatives show the immense possibility for the future. Different types of fiber-reinforced concrete (FRC) and textile reinforced concrete (TRC) specimens are generally investigated for this purpose (Alrshoudi, 2021; Du et al, 2018; Ravikumar et al, 2015; Volkova et al, 2016). Three-point or four-point bending tests are conducted to determine the flexural strength and evaluate the mechanical behavior and performance of the specimens (Colombo et al, 2015; Siddika et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The researchers observed that increasing the diameter of steel springs led to increased shear resistance due to enhanced confinement provided by larger springs. Similarly, a study by Alrshoudi [5] focused on the influence of spring length on the flexural strength of reinforced concrete beams. The team evaluated beams with different spring lengths and discovered that longer springs resulted in greater flexural strength due to improved reinforcing efficacy across a broader span.…”
Section: Introductionmentioning
confidence: 99%